Cell Lysis Method Affects Assessment of Microbial Diversity Based on Ribotyping Analysis - HENI YOHANDINI; FIDA MADAYANTI; PINGKAN ADITIAWATI; . AKHMALOKA (Microbiology Indonesia, 2008)
The microbial community in Kawah Hujan, Kamojang, West Java, Indonesia, was analyzed using 16S-rRNA-gene-sequencing combining with denaturing-gradient-gel electrophoresis (DGGE) technique. Two different cell lysis methods, enzymatic-based, and physical treatment-based DNA extraction, were used to isolate chromosomal DNA for 16S rDNA gene-fragment amplification. The DGGE profiles showed some differences in banding pattern that were obtained from both cell lysis methods. The DNA sequence analysis of the individual DGGE bands revealed that most of the band sequences obtained by physical treatment were close to 16S rRNA gene fragments from the bacterial domain, while most of band sequences performed by enzymatic method had high homology with 16S rRNA gene fragments from archaeal domain. Further analysis of the sequences from both methods performed by comparisons with the Ribosomal Database Project showed that some of DGGE sequences from Kawah Hujan consisted unique 16S rDNA sequences.